PB2-Q591K Mutation Determines the Pathogenicity of Avian H9N2 Influenza Viruses for Mammalian Species - Wang, Congrong (PLoS One, 2016)
BACKGROUND: Influenza A subtype H9N2 is widespread and prevalent in poultry. It has repeatedly transmitted zoonotically to cause mild influenza-like illness in humans and is regarded as a potential pandemic candidate. In additon, the six internal genes of H7N9 and H10N8 viruses which caused infection in human in China as well as some of the highly pathogenic H5N1 strains are origined from H9N2. Previous studies have shown that the mammalian adaptation PB2-Q591K contributes to the pathogenicity of H5N1 and H7N9 viruses. However, the role of the PB2-Q591K mutation in H9N2 subtype is still not well understood. METHODS: To define and compare the individual role of PB2-Q591K substitution in the PB2 gene segment of H9N2 in relation to polymerase activity, replication competence and the pathogenicity using in vitro and in vivo models. RESULTS: The PB2-Q591K mutation in H9N2 virus enhanced the polymerase activity and virus replication in human NHBE cells when compared to the wild type strain. Mice infected with the PB2 mutant showed significant weight loss, higher virus replication and immune responses in the lungs. CONCLUSIONS: Our evidences suggest that the PB2-Q591K, in addition to the -E627K mutation in H9N2 enhanced the pathogenicity in mammalian host.